Assessing effects of sulfate minerals on petroleum generation in sedimentary basins using hydrous pyrolysis: I. Light alkanes. (December 2019) - Chen, Xueze; Liu, Quanyou; Meng, Qingqiang; Zhu, Dongya; Liu, Wenhui; Fu, Qi
Abstract: A series of hydrous pyrolysis experiments were conducted to assess the role of sulfate minerals on the chemical and isotopic compositions of light hydrocarbons generated during thermal degradation of kerogen. The shale source rock with low maturity (Tmax  = 425 °C) from Eagle Ford formation in southeast Texas was used in the experiments at 330 °C for the duration of 72 h, while the abundance of gypsum in each experiment varies from 0, 0.5, to 1 wt%. Under experimental conditions, the positive effect of gypsum on the yields of gaseous alkanes (C1 - C4 ) and CO2 has been explicitly observed, with an exponential relationship between the yield of each gas and the amount of gypsum. While the relative abundance of C2 - C4 alkanes has shown an increasing trend with gypsum, the gas dryness (C1 /∑C1-4 ), however, decreased from 73.1% with no gypsum to 49.6% with gypsum of 1 wt%. It was attributed to lower overall yields and corresponding higher increased generation rates of C2 - C4 alkanes than methane through thermal cracking of kerogen and other organic compounds. The carbon isotope value of each alkane reached the highest in the experiment with 1 wt% gypsum. Compared to the experiment without gypsum, there was an increase of 11.5‰ for the δ 13 C value of methane with 1 wt% gypsum. The extent of this 13 C enrichment between experiments with different amount of gypsum became less for C2 to C4 . The δ 13 C value of CO2 was the highest among generated gases, ranging from −4.7 to −2.1‰. Combined with chemical compositions of gases, it suggested that enhanced thermal cracking reactions were predominant in generation of light alkanes with the presence of gypsum, whereas dissolution of carbonates was the main source of CO2 . The reactions involving thermochemical sulfate reduction (TSR) were minor (if present) under experimental conditions, most likely due to the small quantity of gypsum (up to 1 wt%) and neutralization of acidity by carbonates. Nonetheless, the changes in chemical and isotopic compositions of light alkanes, which were ultimately caused by the presence of gypsum, need to be incorporated into geochemical proxies for assessing source rocks (maturation in particular) and their generation potential. Highlights: Hydrous pyrolysis experiments were conducted to assess the role of gypsum (0-1 wt%) on light hydrocarbon generation. There is a positive effect on the yield of C1 - C4 gaseous alkanes, due to enhanced thermal cracking reactions with gypsum. Each alkane gas becomes enriched in 13 C with gypsum, with the extent of this 13 C enrichment being prominent for methane. The effect of gypsum on chemical and isotopic compositions of light hydrocarbons is important for source rock evaluation.